2013
DOI: 10.5534/wjmh.2013.31.3.215
|View full text |Cite
|
Sign up to set email alerts
|

Can the Mean Platelet Volume Be a Risk Factor for Vasculogenic Erectile Dysfunction?

Abstract: PurposeThe mean platelet volume (MPV) is a marker of the platelet activity and is reported to increase in vascular diseases. We aimed to investigate the association between MPV and vasculogenic erectile dysfunction (ED).Materials and MethodsMPV and platelet (PLT) levels were measured in 50 cases of ED and 40 healthy controls. The diagnosis of vasculogenic ED was based on a detailed sexual history, physical examination, laboratory assessment, and color Doppler ultrasonography. The results are given as mean±stan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
36
0
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(40 citation statements)
references
References 24 publications
2
36
0
2
Order By: Relevance
“…7,8,[16][17][18][19][20] The basis of our study was the suspicion that platelet activation and EC are predictive factors for damaged venoocclusive mechanism and endothelial damage, which has a role in ischemic pathophysiology.…”
Section: -13mentioning
confidence: 99%
See 2 more Smart Citations
“…7,8,[16][17][18][19][20] The basis of our study was the suspicion that platelet activation and EC are predictive factors for damaged venoocclusive mechanism and endothelial damage, which has a role in ischemic pathophysiology.…”
Section: -13mentioning
confidence: 99%
“…It is known to be connected to the atherosclerosis process in penile arterial deficiency. [5][6][7][8] As seen in many studies, platelets play an active role in vascular pathologies. Eosinophils activate the coagulation system and thrombocytes.…”
Section: -13mentioning
confidence: 99%
See 1 more Smart Citation
“…16 MPV increased in ED, however no studies up to date have investigated the relation of PDW with ED. 15,17 In our study, we found higher MPV and PDW in patients who had vascular insufficiency in CDUS (p = 0.011 and p < 0.001; respectively). The difference between the groups for MPV was in correlation with the previous studies.…”
Section: Discussionmentioning
confidence: 46%
“…The difference between the groups for MPV was in correlation with the previous studies. 15,17 Ciftci et al performed a study on 50 patients and 40 controls, and reported that they did not find any correlation of MPV with age of the patient or disease duration. 17 In our study, a correlation was found between the age of the patient and MPV (r = 0.286, p = 0.006).…”
Section: Discussionmentioning
confidence: 96%